EFFORTS TO BUILD A BALANCE OF FAITH, KNOWLEDGE AND CHARITY IN THE INTEGRATIVE PARADIGM OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM - Siti Mamluatul Jannah; Imam Junaris (RADJA PUBLIKA, 2025)
This study aims to analyze in depth the efforts to build a balance of Faith, Knowledge, and Practice in the integrative paradigm of the Islamic Religious Education (PAI) Curriculum in formal educational institutions. The background of the problem is based on the phenomenon of the dichotomy of knowledge that separates general knowledge and religion, which has implications for the moral crisis and low integrity of graduates (Assegaf, 2011: 271). The integrative paradigm is present as an epistemological solution to reunite knowledge under the umbrella of monotheism, making knowledge a means of strengthening faith and guiding good deeds (Al-Attas, 1993: 65; Annisa, 2019: 9). This qualitative research with a Case Study design was conducted in schools/madrasas that consistently implement the integrative PAI curriculum, with research subjects including principals, PAI teachers, general subject teachers, and students. Data were collected through in-depth interviews, participatory observation, and documentation studies, then analyzed using the Miles and Huberman model (2014: 31). The results of the study indicate that the effort to achieve this balance is realized through a holistic curriculum design that explicitly links Islamic Religious Education (PAI) material with science, the transformation of knowledge into practice through a structured habituation program, and the need for close collaboration between teachers. Despite facing the challenges of fragmented material and limited teacher competencies, the success of this effort is highly dependent on visionary school leadership and the implementation of holistic evaluations that measure the cognitive, affective, and psychomotor domains (Faith, Knowledge, and Practice). The study concluded that the successful implementation of an integrative Islamic Religious Education (PAI) curriculum is able to produce Perfect Humans who have harmony between the beliefs of the heart, intellectual intelligence, and moral practice (Daradjat, 2025: 145).